Application of Hydrotropic Solubilization Technique for Quantitative Determination of Aspirin - MAHESHWARI, R.K.; AWASTHI, R. (Asian Journal of Chemistry, 2010)
In the present investigation, 10 M urea solution has been employed to solubilize a poorly water-soluble drug, aspirin for its titrimetric analysis in tablets. Results of analysis by proposed methods were very comparable with those of a standard, British Pharmacopoeial method. Results of analysis have been validated statistically. The proposed method is quicker than pharmacopoeial method, new, rapid, simple, accurate and reproducible.